Safety awareness among workers in Sekolah Agama Rakyat (SAR) in Sungai Petani, Kedah / Mohd Izzan Afiq Rosli and Muhamad Hidayat Ahmad - Rosli, Mohd Izzan; Ahmad, Muhamad Hidayat (2018)
This chapter discusses on the background of the study. Second, it is followed by the problem statements and research questions. After that, it also included research objectives and information regarding the scope of the study for this research. Besides that another section explains on the significant of study and in the last section is about the definition of the key terms and concepts of this research.